Intra-hospital mortality for community-acquired pneumonia in mainland Portugal between 2000 and 2009 - F. Teixeira-Lopes (Pulmonology, 2019)
Introduction: Community-acquired pneumonia (CAP) remains a common and serious infection with wide variability in intra-hospital mortality. Methods: We performed a retrospective analysis of adult patients admitted with CAP in mainland Portugal between the years 2000 and 2009. Results: The intra-hospital mortality rate was 20.4% with deaths in all age groups. The average age of deceased patients was 79.8 years, significantly higher than surviving patients with 71.3 years. Patients aged 50 or more presented a relative risk of death 4.4 times the risk of patients under this age group. Likewise, in patients aged 65 or more the risk of death was 3.2 times the risk of patients <65 years. Men died more at a younger age than women, the men who died were, on average, 4 years younger than women, 78.1 vs 82.1 years old. Relative risk of death in men was 17% higher than women after adjustment for year of admission and age. Conclusion: CAP remains an important cause of hospital mortality in all age groups. Keywords: Community-acquired pneumonia, Mortality, Intra-hospital mortality, Pneumonia, Inpatient mortality